A survey for maintenance of virulent newcastle disease virus-free area in poultry production in Brazil - Orsi,M.A (2010)
In 2003, Brazil was recognized as a pathogenic Newcastle Disease Virus (NDV) strain-free country for commercial poultry. This research was conducted in Brazil between December 2003 and March 2005 to verify the maintenance of this virulent NDV-free status. Serum samples from 5,455 flocks for commercial poultry farms were collected, comprising 81,825 broiler chickens. The farms were located in nine states of the country, grouped in three geographic regions. Serological evidence of NDV infection was detected in 28.8% of the surveyed farms. However, all fifteen viruses isolated and identified as Newcastle Disease Virus (NDV) were characterized as nonpathogenic strains, based on the Intracerebral Pathogenicity Index. These results showed that Brazil preserves the virulent NDV-free status for commercial flocks.